Joint source-channel coding for image transmission based on best wavelet packet - Jun-hong CHEN; Qin-yu ZHANG (Tongxin xuebao)
A novel joint source/channel image coding algorithm was proposed based on the best wavelet packet in a rate-distortion sense.Different from other wavelet packet image coding,the channel and the channel code information were introduced to the source coding,so the proposed algorithm was a joint source-channel coding.The coding of wavelet packet sub-band was bit plane,accorolingly,the bit streams could be good match to UEP.And a WICP-LDPC code was using as a channel code.The simulation results in BSC channel show that,the proposed algorithm is better than the EEP image transmission system.And the proposed algorithm is also better than several other image transmission algorithms,which proposed recently.